The Effectiveness of PKH Fund Allocation in Promoting Educational Advancement Among School-Aged Children in Teja Village - Ainul Bariah; Mukarto Siswoyo (Jurnal Impresi Indonesia, 2026)
The Family Hope Program (PKH) aims to help poor families meet their children's educational needs, but the effectiveness of fund utilization at the village level still requires further investigation. This study aims to analyze the effectiveness of PKH fund allocation in promoting educational advancement among school-aged children in Teja Village, Rajagaluh District, Majalengka Regency. The method used was descriptive qualitative, with data obtained were then analyzed through interviews and observations with beneficiary families, PKH facilitators, and village officials. Data validity was checked using source triangulation. The results indicate that the use of PKH funds in Teja Village has generally been quite effective in helping improve the education of beneficiary children. This assesment in based on Sutrisno’s effectiveness indicators, such as goal achievement, program understanding, timeliness, targeted accuracy, and tangible changes. However, several obstacles remain, such as uneven understanding of the program’s objectives among beneficiary families and limited ability to manage funds for their children’s education needs. This means that the utilization of PKH funds still needs to be improved, especially through the role of assistants and ongoing outreach.